Pre-Trial Settlement and the Value of Audits - Zhang, Ping; Thoman, Lynda (The Accounting Review, 1999)
This paper studies the impact of liability rules and damage awards on audit effort and the value of an audit (the net benefits to society of an audit) when an auditor and an investor may settle before proceeding to trial. It is demonstrated that audit effort increases with size of the damage award, but may decrease with the rigor of the auditing standards. For a given level of damage award, allowing pre-trial settlements may reduce the value of the audit despite the reduction in the deadweight legal costs. On the other hand, if the damage award is optimally chosen, then allowing settlements increases social welfare. With an appropriately set damage award, strict liability standards result in the first-best outcome, while the first-best result cannot be obtained with vague negligence rules.